2016
DOI: 10.1016/j.ihj.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

A Study to derive distribution of carotid intima media thickness and to determine its COrrelation with cardiovascular Risk factors in asymptomatic nationwidE Indian population (SCORE-India)

Abstract: This is the first study to provide age- and gender-specific distribution of CIMT in Indian subjects free from CVD. This information should help facilitate further research and clinical work involving CIMT in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…But a recent SCORE-India study highlights that the CIMT values were also higher in diabetic subjects at (0.635 ± 0.10 mm) as compared to nondiabetics (0.589 ± 0.12 mm). 30 Hence our observations are consistent with the above nationwide SCORE-India study. Our study shows that the mean CIMT in the silent MI positive group was 0.713 ± 0.021 mm as compared to 0.662 ± 0.028 mm in the negative group.…”
Section: Discussionsupporting
confidence: 91%
“…But a recent SCORE-India study highlights that the CIMT values were also higher in diabetic subjects at (0.635 ± 0.10 mm) as compared to nondiabetics (0.589 ± 0.12 mm). 30 Hence our observations are consistent with the above nationwide SCORE-India study. Our study shows that the mean CIMT in the silent MI positive group was 0.713 ± 0.021 mm as compared to 0.662 ± 0.028 mm in the negative group.…”
Section: Discussionsupporting
confidence: 91%
“…Over more than two decades, CIMT has been extensively researched and established. Moreover, several large, research-based cohort studies have clearly indicated a relationship between CIMT and CV events 21, 22, 23, 24, 25, 26, 27, 28, 29. Carotid plaque, defined as a focal abnormal wall thickness (CIMT > 1.5 mm) or a focal thickening of >50% of the surrounding CIMT has been shown to be a more powerful predictor of CV risk compared with CIMT alone.…”
Section: The Role Of Cimt As Screening Techniquementioning
confidence: 99%
“…The CIMT and aortic stiffness were high in cHypoPT patients with CAD and CAC, respectively. Interestingly, the CIMT value was above the cutoff of healthy Indians in only one cHypoPT with CAD 33 . CIMT did not correlate with serum total calcium or phosphorus at presentation or during follow‐up.…”
Section: Discussionmentioning
confidence: 82%